Conics from the Cartan Decomposition of SO(2,1) - Mircea Crasmareanu (Mathematics, 2023)
The aim of this paper is to introduce and study the class of conics provided by the symmetric matrices of the Cartan decomposition of the Lie group <semantics>SO(2,1)</semantics>. This class depends on two real parameters as components of the cylinder <semantics>S1×R</semantics> and we use a deformation inspired by Finsler indicatrices in order to obtain proper ellipses. A complex approach is also included.